Arterial Stiffness and Left Ventricular Diastolic Function in Endurance Athletes - Hashimoto, Yuto; Okamoto, Takanobu (International Journal of Sports Medicine, 2020)
The present study investigated the relationship between arterial stiffness and left ventricular diastolic function in endurance-trained athletes. Sixteen young male endurance-trained athletes and nine sedentary of similar age men participated in this study. Resting measures in carotid-femoral pulse wave velocity were obtained to assess arterial stiffness. Left ventricular diastolic function was assessed using 2-dimensional echocardiography. The athletes tended to have lower arterial stiffness than the controls (P=0.071). Transmitral A-waves in the athletes were significantly lower (P=0.018) than the controls, and left ventricular mass (P=0.034), transmitral E-wave/A-wave (P=0.005) and peak early diastolic mitral annular velocity at the septal site (P=0.005) in the athletes were significantly greater than the controls. A significant correlation was found between arterial stiffness and left ventricular diastolic function (E-wave: r=− 0.682, P=0.003, E-wave/A-wave: r=− 0.712, P=0.002, peak early diastolic mitral annular velocity at the septal site: r=− 0.557, P=0.025) in the athletes, whereas no correlation was found in controls. These results suggest that lower arterial stiffness is associated with higher left ventricular diastolic function in endurance-trained athletes.
Keywords: pulse wave velocity; echocardiography; athlete’s heart; endurance